The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.35759/jabs.v144.8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation du niveau de transfert de métaux lourds (cadmium, cuivre, plomb et zinc) dans Lactuca sativa L. co-cultivée avec Cymbopogon citratus (DC) Stapf

Abstract: Evaluation du niveau de transfert de métaux lourds (cadmium, cuivre, plomb et zinc) dans Lactuca sativa L. co-cultivée avec Cymbopogon citratus (DC) Stapf

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results for physicochemical characteristics showed that the pH measured in soil showed an acidic pH of about 5.09 at a temperature of 17.70˚C. This result promotes the trophic transfer of heavy metals [25].…”
Section: Study Of the Physicochemical Parameters Of The Soil Samplementioning
confidence: 87%
“…The results for physicochemical characteristics showed that the pH measured in soil showed an acidic pH of about 5.09 at a temperature of 17.70˚C. This result promotes the trophic transfer of heavy metals [25].…”
Section: Study Of the Physicochemical Parameters Of The Soil Samplementioning
confidence: 87%